Congenital lung malformations: correlation between prenatal and postnatal imaging and pathological findings. Issue 3 (July 2016) - Lecompte, Jean-François; Gondran-Tellier, Bastien; Hery, Geraldine; Sikavi, Daniel; Colavolpe, Nathalie; Guys, Jean-Michel; de Lagausie, Pascal
Abstract : Aim: Congenital lung malformations are a common finding during prenatal ultrasonography (US). Investigations were completed by means of prenatal MRI and postnatal computed tomographic (CT) scan. The purpose of this study was to compare these prenatal findings with postnatal findings and pathological findings after surgical resection. Materials and methods: Prenatal examinations and postnatal CT scan results of congenital malformations were compared with pathological findings. Results: From 2007 to 2013, 39 prenatally diagnosed congenital lung malformations were resected: 18 congenital cystic adenomatoid malformation, eight pulmonary sequestration, five bronchogenic cyst, one bronchial atresia and six complex lesions. Correlation between imaging and diagnosis was as follows: congenital cystic adenomatoid malformation was seen in 17/17 patients using postnatal CT, in 10/15 patients using prenatal MRI and in 17/18 patients using prenatal US. Correlation between imaging and diagnosis was as follows: bronchogenic cyst was seen in 3/5, 3/5 and 3/5 patients, pulmonary sequestration was seen in 7/9, 5/9 and 4/9 patients, and complex lesion was seen in 4/5, 3/6, and 2/6 patients using postnatal CT, prenatal MRI, and prenatal US, respectively. Overall, 32/37 cases were diagnosed by means of postnatal CT, 21/36 cases were diagnosed by means of prenatal MRI and 26/39 cases were diagnosed by means of prenatal US. Conclusion: Discordance between imaging data and definitive diagnosis is not rare. Our results suggest that postnatal CT scan is the most sensible and specific examination. Before birth, US seems better compared with MRI for description of the lesion. MRI seems to be useful in case of complex lesions and pulmonary sequestration.